The Talent Thief - (:unkn) unknown (My University, 2014)
The Talent Thief narrates an amateur con artist's philanthropic efforts in Windhoek, Namibia, and her psychological struggle with the guilt of a past crime. Guided by a literalistic interpretation of the Biblical "Parable of the Talents," Callie Donne works to redeem herself and restore her mother's reputation with a high-profile charity fundraising event. The novel's plot echoes elements of the United States' involvement in the economic and political development of the African continent. In its themes and settings, it also offers a point of contact between the Lutheran tradition and post-colonial cultural scholarship for contemporary American readers.